Investigating CNS distribution of PF‐05212377, a P‐glycoprotein substrate, by translation of 5‐HT6 receptor occupancy from non‐human primates to humans. (13th March 2023) - Sawant‐Basak, Aarti; Chen, Laigao; Lockwood, Peter; Boyden, Tracey; Doran, Angela C.; Mancuso, Jessica; Zasadny, Kenneth; McCarthy, Timothy; Morris, Evan D.; Carson, Richard E.; Esterlis, Irina; Huang, Yiyun; et al.
Abstract: PF‐05212377 (SAM760) is a potent and selective 5‐HT6 antagonist, previously under development for the treatment of Alzheimer's disease. In vitro, PF‐05212377 was determined to be a P‐gp/non‐BCRP human transporter substrate. Species differences were observed in the in vivo brain penetration of PF‐05212377 with a ratio of the unbound concentration in brain/unbound concentration in plasma (Cbu /Cpu ) of 0.05 in rat and 0.64 in non‐human primates (NHP). Based on pre‐clinical evidence, brain penetration and target engagement of PF‐05212377 was confirmed in NHP using positron emission tomography (PET) measured 5‐HT6 receptor occupancy (%RO). The NHP Cpu EC50 of PF‐05212377 was 0.31 nM (consistent with the in vitro human 5HT6 Ki : 0.32 nM). P‐gp has been reported to be expressed in higher abundance at the rat BBB and in similar abundance at the BBB of non‐human primates and human; brain penetration of PF‐05212377 in humans was postulated to be similar to that in non‐human primates. In humans, PF‐05212377 demonstrated dose and concentration dependent increases in 5‐HT6 RO; maximal 5‐HT6 RO of ∼80% was measured in humans at doses of ≥15 mg with an estimated unbound plasma EC50 of 0.37 nM (which was similar to the in vitro human 5HT6 binding Ki 0.32 nM). In conclusion, cumulative evidence from NHP and human PET RO assessments confirmed that NHP is more appropriate than the rat for the prediction of human brain penetration of PF‐05212377, a P‐gp/non‐BCRP substrate. Clinical trial number: NCT01258751. Abstract : PF‐05212377 (5HT6 Ki : 0.32 nM) was determined to be a P‐gp/non‐BCRP substrate. As P‐gp is expressed in similar abundance at the BBB of non‐human primates (NHP) and human, brain penetration of PF‐05212377 in humans was postulated to be similar to NHP. Target engagement was investigated in NHP, using PET RO. In humans, PF‐05212377 demonstrated concentration dependent increases in 5‐HT6 RO confirming that NHP was more appropriate than rat for the evaluating the CNS distribution of PF‐05212377.